The E3 ubiquitin ligase CHIP in normal cell function and in disease conditions. Issue 1 (15th August 2019) - Wang, Tingyu; Wang, Wenbo; Wang, Qishan; Xie, Rong; Landay, Alan; Chen, Di
Abstract: In eukaryotic cells, ubiquitination and proteasomal degradation is an essential mechanism for regulating protein functions. For example, critical signaling proteins play their roles by controlling different cellular functions. Once a signaling protein has been activated, its activity needs to be quickly downregulated by different mechanisms, including ubiquitination/proteasome regulation. Failure to regulate the activity or expression levels of these proteins may cause human diseases. Protein ubiquitination involves a cascade of biochemical processes and requires three types of ubiquitin enzymes: E1 activating enzyme, E2 conjugating enzyme, and E3 ligase. Among these enzymes, E3 ubiquitin ligases play a specific role in recognizing specific protein substrates. There are several structurally diverse groups of E3 ubiquitin ligases in eukaryotic cells, and one type of these E3 ligases is the U‐box ubiquitin ligases. Carboxyl terminus of HSP70‐interacting protein (CHIP) is a member of a family of U‐box E3 ligases. It plays critical roles in multiple organs and tissues in the body. In this review article, we provide an update on some of the most recent discoveries about CHIP in normal physiological function and in disease. Abstract : Carboxyl terminus of HSP70‐interacting protein (CHIP) is a member of a family of U‐box E3 ligases that are involved in protein ubiquitination. It plays critical roles in multiple organs and tissues in the body. In this review article, the authors provide an update on some of the most recent discoveries about CHIP in normal physiological function and in disease.